Manajemen Produksi Iklan Radio Dan Perancangan Sistem Penentuan Biaya Iklan Pada OZ Radio 90.8 FM Jakarta - Muhammad Rizky Ramadhan; Daniel Handoko; Jamiati KN; Velda Murdiana (Universitas 45 Surabaya, 2024)
Radio advertising is a type of advertising that is quite popular and effective for promoting products or services. However, to optimize the effectiveness of radio advertising, good radio advertising production analysis and an appropriate advertising cost determination system are needed. The research entitled